A Review and Update on Clinical Management on Burning Mouth Syndrome - Juliana Cassol Spanemberg; Eugenia Rodríguez de Rivera Campillo; Enric Jané Salas; Albert Estrugo Devesa; José López López (New Frontiers in Medicine and Medical Research Vol. 16, 2021)
Burning Mouth Syndrome (BMS) is a persistent condition that primarily affects postmenopausal middle-aged women. The absence of clinical indications and burning feelings of the oral mucosa identify this illness.BMS has a complicated aetiology that incorporates a number of factors.BMS can be caused by a variety of local, systemic, and psychological conditions, including stress, anxiety, and depression. BMS Type I, II, or III are possible classifications. Although there are no obvious organic changes and no health hazards associated with this illness, it can drastically affect the patient’s quality of life. The objective is to review the available literature related to BMS, and makes special reference to its therapeutic management. The sections that follow will also go through important diagnostic criteria, etiological factors, and clinical aspects. The main objective of management is that of providing support to the patient and working towards symptom reduction, rather than total elimination of such symptoms. Tricyclic antidepressants, benzodiazepines, and antipsychotic medicines are the most frequently accepted therapy alternatives with variable results; nevertheless, there are other therapies that will be presented that can also be used. The management of this group of patients should be done by professionals who talk and reaffirm to them the nature of the disease and discuss the benefits of intended therapies or possibility of pain relief. Patients should be educated about the need for a multidisciplinary team approach and the probability of needing multiple changes in therapies until effective treatment is achieved. Professionals in the field of dentistry should develop standardised symptoms and diagnostic criteria so that multidisciplinary research can more easily discover the most successful and reliable BMS treatment techniques.